Accelerated partial breast irradiation utilizing brachytherapy: patient selection and workflow - Shah, Chirag; Wobb, Jessica; Manyam, Bindu; Khan, Atif; Vicini, Frank (Journal of Contemporary Brachytherapy, 2016)
Accelerated partial breast irradiation (APBI) represents an evolving technique that is a standard of care option in appropriately selected woman following breast conserving surgery. While multiple techniques now exist to deliver APBI, interstitial brachytherapy represents the technique used in several randomized trials (National Institute of Oncology, GEC-ESTRO). More recently, many centers have adopted applicator-based brachytherapy to deliver APBI due to the technical complexities of interstitial brachytherapy. The purpose of this article is to review methods to evaluate and select patients for APBI, as well as to define potential workflow mechanisms that allow for the safe and effective delivery of APBI. Multiple consensus statements have been developed to guide clinicians on determining appropriate candidates for APBI. However, recent studies have demonstrated that these guidelines fail to stratify patients according to the risk of local recurrence, and updated guidelines are expected in the years to come. Critical elements of workflow to ensure safe and effective delivery of APBI include a multidisciplinary approach and evaluation, optimization of target coverage and adherence to normal tissue guideline constraints, and proper quality assurance methods.